2014
DOI: 10.1089/brain.2014.0326
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Resting-State fcMRI Networks by Prior Sensory Stimulation

Abstract: It is important to consider the effect of a previous experimental condition when analyzing resting-state functional connectivity magnetic resonance imaging (fcMRI) data. In this work, a simple sensory stimulation functional MRI (fMRI) experiment was conducted between two resting-state fcMRI acquisitions in anesthetized rats using a high-field small-animal MR scanner. Previous human studies have reported fcMRI network alteration by prior task/stimulus utilizing similar experimental paradigms. An anesthetized ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Stimulation parameters were adapted from N. Van Camp et al [23] and included current pulses with a 1.7 mA amplitude, 10 ms duration and 8 Hz frequency applied in a block-design. In a separate experiment outside the magnet, 1.7 mA-current intensity was found to be below the threshold of nociception (S1 Table), where no significant changes in cardiac frequency and pulse oximetry were observed while applying stimulation under our conditions of anesthesia [12,35,36]. As reported by N. Van Camp et al [23] and observed in the present study, this set of electrical stimulation parameters resulted both in somatosensory and proprioceptive inputs owing to visible movement in the hindpaw's digits (S1 Video).…”
Section: Methodsmentioning
confidence: 84%
“…Stimulation parameters were adapted from N. Van Camp et al [23] and included current pulses with a 1.7 mA amplitude, 10 ms duration and 8 Hz frequency applied in a block-design. In a separate experiment outside the magnet, 1.7 mA-current intensity was found to be below the threshold of nociception (S1 Table), where no significant changes in cardiac frequency and pulse oximetry were observed while applying stimulation under our conditions of anesthesia [12,35,36]. As reported by N. Van Camp et al [23] and observed in the present study, this set of electrical stimulation parameters resulted both in somatosensory and proprioceptive inputs owing to visible movement in the hindpaw's digits (S1 Video).…”
Section: Methodsmentioning
confidence: 84%
“…In this study, task fMRI was conducted before resting fMRI. A previous study suggested that sensory stimulation prior to resting fMRI could enhance functional connectivity between the sensory, insular and limbic cortices (Li et al, 2014). Therefore the observed connectivity may have been modulated by the somatosensory stimulation applied.…”
Section: Limitationsmentioning
confidence: 93%
“…To avoid this problem, there have been some reports of preclinical imaging using pharmacological MRI, fluorine-18-fluorodeoxyglucose ( 18 F-FDG)-PET and 99m Tc-hexamethylpropylene amine oxime (HMPAO)-SPECT in conscious animals 11 14 . However, in most of these studies, the animals are exposed to the stress of physical restraint, which has a huge effect on the brain function 15 17 .…”
Section: Introductionmentioning
confidence: 99%